2019
DOI: 10.1007/s00125-019-04976-w
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-associated metabolic signalling networks in pancreatic beta cell function

Abstract: Significant advances have been made in deciphering the mechanisms underlying fuel-stimulated insulin secretion by pancreatic beta cells. The contribution of the triggering/ATP-sensitive potassium (K ATP)-dependent Ca 2+ signalling and K ATP-independent amplification pathways, that include anaplerosis and lipid signalling of glucose-stimulated insulin secretion (GSIS), are well established. A proposed model included a key role for a metabolic partitioning 'switch', the acetyl-CoA carboxylase (ACC)/malonyl-CoA/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 75 publications
0
43
1
1
Order By: Relevance
“…25 This leads to hepatic steatosis that is further exacerbated if chronically excessive carbohydrate or medium chain triglyceride is given. 26,27 10/14 severe patients surviving infancy had evidence of steatohepatitis, 2/14 with gallstones and 1/14 developed liver fibrosis by 10 years of age. The hyperammonaemia in this patient (case 8) appeared less responsive to acute carbohydrate administration, possibly related to the reduction in GS expression in patients with liver cirrhosis.…”
Section: T a B L E 3 (Continued)mentioning
confidence: 99%
“…25 This leads to hepatic steatosis that is further exacerbated if chronically excessive carbohydrate or medium chain triglyceride is given. 26,27 10/14 severe patients surviving infancy had evidence of steatohepatitis, 2/14 with gallstones and 1/14 developed liver fibrosis by 10 years of age. The hyperammonaemia in this patient (case 8) appeared less responsive to acute carbohydrate administration, possibly related to the reduction in GS expression in patients with liver cirrhosis.…”
Section: T a B L E 3 (Continued)mentioning
confidence: 99%
“…In these mice we see impaired in vivo insulin responses to glucose, but this may be compensated for in part by an increased fasting insulin (Suppl Fig 1) thus limiting glucose intolerance in the absence of metabolic stress. We should also recognize that other pathways facilitating insulin secretion could compensate for the loss of SENP1 in vivo, for example lipid-mediated signaling 32,33 , which may be minimized in in vitro experiments performed in minimal buffers without fatty acid. Nonetheless, high fat feeding revealed the importance SENP1-dependent insulin secretion in the maintenance of glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…GDM is strongly correlated with fetal growth [37], but neonatal hypoglycemia was negative with different fetal carnitine levels in our study. Most studies reported that carnitine was associated with the development and progress of diabetes mellitus for multiperspectives such as microbiota [38] and lipid [39].…”
Section: Discussionmentioning
confidence: 99%